2023
DOI: 10.3389/fchem.2023.1154128
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria assisted green synthesis of copper oxide nanoparticles and their potential applications as antimicrobial agents and plant growth stimulants

Abstract: Copper oxide nanoparticles (CuO-NPs) have piqued the interest of agricultural researchers due to their potential application as fungicides, insecticides, and fertilizers. The Serratia sp. ZTB29 strain, which has the NCBI accession number MK773873, was a novel isolate used in this investigation that produced CuO-NPs. This strain can survive concentrations of copper as high as 22.5 mM and can also remove copper by synthesizing pure CuO-NPs. UV-VIS spectroscopy, DLS, Zeta potential, FTIR, TEM, and XRD techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Consistent with this, another study on soybean reported the improvement of plant growth under copper stress mediated by release of nitric oxide by chitosan nanoparticles [ 105 ]. Similarly, considering the biocompatibility and antimicrobial properties of silver and copper, their nanoparticles have been widely used in the amelioration of various biotic stressors [ 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ].…”
Section: Nanoparticles and Antioxidant Systemmentioning
confidence: 99%
“…Consistent with this, another study on soybean reported the improvement of plant growth under copper stress mediated by release of nitric oxide by chitosan nanoparticles [ 105 ]. Similarly, considering the biocompatibility and antimicrobial properties of silver and copper, their nanoparticles have been widely used in the amelioration of various biotic stressors [ 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ].…”
Section: Nanoparticles and Antioxidant Systemmentioning
confidence: 99%
“…The dried sample was grounded and calcined for three hours at 500°C. The material was granulated and placed in a container after it reached room temperature (Singh et al 2023) (Figure 1).…”
Section: Preparation Of Cuo Nanoparticlesmentioning
confidence: 99%
“…These dyes impede the flow of oxygen and light into water. Reactive black is a dye consumed extensively for reactive dying (Singh et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Biosynthesized CuO NPs have been prepared from leaf extract of Eucaliptus globulos [ 58 ], mint leaves and orange peels [ 59 ], algae ( Anabaena cylidrica ) [ 60 ], and bacteria ( Serratia sp.) [ 61 ], usually by using copper sulfate salt precursor. The biosynthesized CuO NPs are thought to have increased antimicrobial activity compared to commercial NPs due to the participation of natural extracts used for reduction [ 3 ].…”
Section: Characteristics Of Some Biosynthesized Npsmentioning
confidence: 99%